IMPROVING THE MENTAL HEALTH OF LGBTQ YOUTH: A SHORT NARRATIVE REVIEW OF SPECIFIC INTERVENTIONS - Georgiana LĂZĂRESCU; Adina KARNER-HUȚULEAC; Alexandra MAFTEI (Association of Social and Educational Innovation, 2023)
Previous studies concerning LGBTQ individuals' experiences found significant challenges, including discrimination, prejudice, and violence. Given these experiences, researchers are preoccupied with the examination of the potential adverse effects on the physical and mental health of LGBTQ individuals and the effective strategies to reduce these negative outcomes. In this short narrative review, we discuss some of the specific interventions aimed to improve the mental health of LGBTQ individuals, especially among the youth. More specifically, we discuss the theoretical framework and empirical evidence related to LGBTQ - Affirmative Cognitive-Behavioral Therapy, Creative Writing and Expressive Wiring Therapy, Attachment-based Family Therapy, and LGBTQ Relationally - based Positive Psychology.